2022
DOI: 10.5468/ogs.21313
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and predictive factors for recurrent clear cell ovarian carcinoma: results from a single center in Thailand

Abstract: We aimed to study the incidence and predictive factors of recurrent clear cell ovarian carcinoma (CCC) and evaluate the oncological outcomes after recurrence. MethodsThis was a retrospective study of 134 CCC cases diagnosed between 2005 and 2020.Clinicopathological data and oncological outcomes were extracted and evaluated. Patients with comalignancy, mixed pathological type, or incomplete data were excluded. Descriptive statistics, univariate and multivariable analyses, and Kaplan-Meier survival probability e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…This type of cancer often affects younger patients. Hemman and Rattanaburi conducted a study in the Thai population and found that patients with recurrent PRCCC who received an additional line of chemotherapy had an estimated survival time of 7.8 months [ 17 ]. The results of our patient align with these findings, as she had a progression-free survival of 2 months and an overall survival of 8.5 months.…”
Section: Discussionmentioning
confidence: 99%
“…This type of cancer often affects younger patients. Hemman and Rattanaburi conducted a study in the Thai population and found that patients with recurrent PRCCC who received an additional line of chemotherapy had an estimated survival time of 7.8 months [ 17 ]. The results of our patient align with these findings, as she had a progression-free survival of 2 months and an overall survival of 8.5 months.…”
Section: Discussionmentioning
confidence: 99%